STOCK PRICE PREDICTION USING AI & ML - Mahi Singh; Kanishka Jain; Dev Kumar Singh; Deepak Kumar; Dr. Pawan Kumar Mall (IJRDO -Journal of Computer Science Engineering, 2025)
In the financial sector, forecasting stock prices is a crucial responsibility as it helps traders and investors make well-informed decisions. The intricacy and fluctuations of financial markets provide formidable obstacles. For precisely capturing complex market dynamics conventional forecasting techniques like technical analysis and econometric models are inadequate. These traditional methods frequently depend on past price trends and oversimplified statistical correlations. Artificial intelligence has grown and computing power has expanded. Now Al based prediction techniques have become more effective at forecasting stock values. This study examines the artificial intelligence role in stock prices Prediction. We provide a thorough summary of the literature in this field classifying different types of prediction models and comparative analysis of previous work done.